The Effect of Cooperative Learning on Intensive Reading of Short Stories - Murni Efriyanti; Eko Firman Susilo; Saprida (INTERACTION: Jurnal Pendidikan Bahasa, 2025)
This quasi-experimental study aims to determine the effect of the Cooperative Learning method on students' intensive reading ability in analyzing short story elements at SMA Negeri 2 Rantau Selatan. The study addresses the problem of students' low ability to understand and analyze the intrinsic elements of short stories, such as theme, plot, characters, setting, and moral. Using a quantitative approach, the research involved two classes: an experimental class and a control class, each consisting of 30 students. The instrument used was an intensive reading test (pretest and posttest). The results showed a significant improvement in the intensive reading ability of students in the experimental class after applying the Cooperative Learning method. The average pretest score of the experimental class was 65.2, increasing to 82.5 in the posttest. In contrast, the control class's scores increased from 64.8 to 72.1. The t-test results indicated a significance value of 0.000 < 0.05, showing a significant difference between the experimental and control groups. Therefore, it can be concluded that the Cooperative Learning method has a positive and significant effect on students’ intensive reading ability. The findings suggest that Cooperative Learning is an effective approach to improving students’ analytical skills in reading short stories, as it fosters collaboration and active engagement with the text. Considering these results, educators are encouraged to incorporate Cooperative Learning strategies into their teaching practices, particularly in reading instruction, to enhance students’ comprehension and critical thinking skills. Additionally, this research implies that Cooperative Learning can be an effective tool to address the challenges students face in understanding complex texts and can be adapted for various subjects and grade levels.